Non-mobile Adjacent Level Cervical Spondylolisthesis Does Not Always Require Fusion in Patients Undergoing ACDF. Issue 18 (15th September 2019) - Segar, Anand H.; Divi, Srikanth N.; Tarazona, Daniel; Fried, Tristan; Sandhu, Hanna; Kaye, Ian D.; Kepler, Christopher K.; Kurd, Mark F.; Woods, Barrett I.; Hilibrand, Alan S.; Radcliff, Kristen E.; Rihn, Jeffrey A.; et al.
Abstract : Study Design: Retrospective review of a prospectively maintained database. Objective: Compare outcomes following anterior cervical decompression and fusion (ACDF) between patients with no adjacent level spondylolisthesis (NAS) and adjacent level spondylolisthesis (AS). Summary of Background Data: There are no prior studies evaluating the effect of preoperative adjacent-level cervical spondylolisthesis on outcomes following anterior cervical discectomy and fusion (ACDF). Methods: A retrospective review of consecutive patients who underwent ACDF for degenerative cervical disease was performed. Adjacent level spondylolisthesis was defined on radiographs as anterior displacement (> 1 mm) of the vertebra in relation to an adjacent "to be fused" level. Patients were categorized as either AS or NAS. Preoperative and 1-year postoperative outcomes including Short Form-12 Physical and Mental Component Scores, Neck Disability Index, Visual Analog Score for arm and neck pain, and rate of revision surgery were compared between the two groups. Radiographic changes were also analyzed for patients with AS. Results: A total of 264 patients met the inclusion criteria. There were 53 patients (20.1%) with AS and 211 patients (79.9%) with NAS. Both groups improved significantly from baseline with respect to all patient outcomes and there were no significant differences between the two groups. After accounting for confounding variables, the presence of an AS was not a predictor of any postoperative outcome. Revision rates did not differ between the two groups. Conclusion: Patients with an AS had similar postoperative clinical outcomes compared with NAS. Furthermore, the presence of an AS was not a predictor of poorer clinical outcomes. This is the first study to investigate the effect of AS in patients undergoing ACDF and suggests that an adjacent-level spondylolisthesis does not need to be included in a fusion construct if it is not part of the primary symptom generating pathology. Level of Evidence: 3 Abstract : The optimal management of degenerative cervical spondylolisthesis adjacent to other cervical pathology is unclear. In patients undergoing ACDF, adjacent-level spondylolisthesis had similar postoperative clinical outcomes compared to those without one. Our findings suggest that adjacent-level spondylolistheses do not need to be included in the fusion construct if they do not contribute to the neurologic symptoms.